GENDER AND DISABILITY: A STUDY WITH SPECIAL REFERENCE TO WOMEN - Surjan, Praveen Kumar; Gautam, Akhilesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Gender and disability are both societal constructs. Both ideas entail various preconceptions that establish expectations and limitations regarding them. These expectations and restrictions can generate issues about identity development among those with disabilities. This research seeks to elucidate various social expectations and restrictions while providing a concise explanation of the ideas of gender and disability. This research seeks to examine the correlation between gender and disability, as well as to identify the factors that influence these correlations. This paper examines the societal issues associated with disability notably concerning women and proposes potential solutions. This paper analyses in-depth interviews conducted with women from three distinct age groups, framed around research questions derived from a review of numerous studies concerning gender, disability, and the intersection of women and disability.